2014
DOI: 10.1111/gcb.12672
|View full text |Cite
|
Sign up to set email alerts
|

Carbon accumulation of tropical peatlands over millennia: a modeling approach

Abstract: Tropical peatlands cover an estimated 440,000 km2 (~10% of global peatland area) and are significant in the global carbon cycle by storing about 40-90 Gt C in peat. Over the past several decades, tropical peatlands have experienced high rates of deforestation and conversion, which is often associated with lowering the water table and peat burning, releasing large amounts of carbon stored in peat to the atmosphere. We present the first model of long-term carbon accumulation in tropical peatlands by modifying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 67 publications
5
81
1
2
Order By: Relevance
“…Several other studies have shown a leveling off of soil CO 2 efflux at very low water tables (25,26), and it is also likely that very high water tables ultimately limit net carbon uptake by trees (primary production) (16). However, including these effects did not affect simulations because these extreme water table heights and depths were neither observed at our site nor predicted by simulations of our site.…”
Section: Methodscontrasting
confidence: 50%
See 2 more Smart Citations
“…Several other studies have shown a leveling off of soil CO 2 efflux at very low water tables (25,26), and it is also likely that very high water tables ultimately limit net carbon uptake by trees (primary production) (16). However, including these effects did not affect simulations because these extreme water table heights and depths were neither observed at our site nor predicted by simulations of our site.…”
Section: Methodscontrasting
confidence: 50%
“…9 A and E), which is a recognized climate feedback for tropical peatlands (12), and also show that artificial drainage for agriculture (Fig. 9D) can dominate all natural feedbacks if not curtailed (4,16). In addition, our simulations demonstrate a third feedback: The increase in rainfall variability from warming climates (33) can cause peat loss if not compensated by an increase in total rainfall ( Fig.…”
Section: Dynamics Of Tropical Peatland Topography and Carbon Fluxesmentioning
confidence: 54%
See 1 more Smart Citation
“…A modelling approach in Ref. [13] also confirms the continuity of these predictions for decades. Soil degradation of peatlands is also one result of the artificial drainage.…”
supporting
confidence: 57%
“…In natural conditions, the portion of SOM that is decomposed and emitted as carbon dioxide (CO 2 ) or methane (CH 4 ) is usually outweighed by the continuous input of fresh litter and roots (Jauhiainen et al 2005;Hergoualc'h and Verchot 2011;Hoyos-Santillan et al 2015). Models such as the Holocene Peat Model-HPM (Frolking et al 2010;Kurnianto et al 2015) use this balance to predict long-term peat accumulation via vegetation-specific characteristics such as decomposition speed and primary production.…”
Section: Introductionmentioning
confidence: 99%